STRATEGI PENINGKATAN HASIL KELULUSAN UJI KOMPETENSI PENYULUH KB DALAM PELAYANAN PROGRAM BANGGA KENCANA DI MASYARAKAT - Absyari, Amalia (Jurnal Progress Administrasi Publik, 2025)
This study focuses on the low pass rate of the Family Planning Extension (KB) competency test in South Kalimantan Province, which is the main concern is efforts to improve the quality of family planning services. The main purpose of this study is to analyze the strategies implemented by the BKKBN Representative Office of South Kalimantan Province in improving graduation outcomes and identifying internal and external factors that affect the graduation. This study uses a qualitative method with a descriptive approach, utilizing primary and secondary data collected through observation, in-depth interviews, and documentation. The results of this study show that the strategies implemented have not been effective, especially due to the lack of commitment in training and coaching the performance of Family Planning Extension Workers, as well as the lack of integrated and coordinated action actions in monitoring and evaluation. Internal factors that affect graduation include minimal knowledge and skills, physical condition, motivation, and work discipline of Family Planning Extension Workers. Meanwhile, external factors include changes in teachers, changes in learning methods, limited facilities and infrastructure, and inadequate budgets. This study recommends that the BKKBN Representative Office facilitate Family Planning Extension Workers with media containing competency test questions, build a strong commitment with OPD KB as a strategic partner, and develop integrated and coordinated action actions in the internal scope to achieve a significant increase in graduation rates.   Keywords: Competency Test; Family Planning Extension  Strategy